Implementasi Kurikulum Merdeka dalam Praktik Pembelajaran Merdeka Belajar - Jesika Aprilian Purba Siboro; Helena Zepania Samosir; Fibra Ananta; Clara Theresia Lumbantoruan; Antonia Lioncun br. Sitorus; Christa Voni Roulina Sinaga (Young Journal of Social Sciences and Humanities, 2025)
This research aims to examine conceptually how the Independent Curriculum is implemented in learning practices in schools, especially in shaping student character through the dimension of the Pancasila Student Profile. This study uses a literature study method with a descriptive-qualitative approach, which combines the analysis of policy documents and the study of educational theory. The results of the study show that the Independent Curriculum presents a learning system that is oriented to the principle of "independent learning", which provides freedom for students to explore their potential according to their interests, talents, and learning needs. The teaching tools used, such as the Pancasila Student Profile Strengthening Project, not only support academic aspects, but also instill spiritual, social, and moral values in depth. Thus, learning in the Independent Curriculum not only focuses on the transfer of knowledge, but also the formation of a whole human being who has a strong spiritual foundation and is able to contribute to the life of the wider society.